2021
DOI: 10.1007/s12144-021-01529-6
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the psychosocial impact of COVID-19 lockdown in post-bariatric surgery women: the importance of eating behavior, health care access, and social support

Abstract: This study aims to characterize the psychosocial impact of COVID-19 lockdown for post-bariatric surgery (≥ 36 months) women and its association with disordered eating and psychological distress. The medium to long-time follow up is a period of increased susceptibility for poorer weight outcomes which might be triggered by the lockdown. Twenty-four participants responded to an online questionnaire and a telephone interview. About half ( n = 14; 58.3%) reported perceived weight gain during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…Similar to other studies on patients who have undergone BS, a subjective increase in weight was observed in the vast majority of our patients (86%) [ 40 , 41 ], even from very early on in the pandemic [ 42 ]. A study on the 3-year evolution of BS patients during the pandemic compared to prior to the pandemic also showed less weight loss during the pandemic [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to other studies on patients who have undergone BS, a subjective increase in weight was observed in the vast majority of our patients (86%) [ 40 , 41 ], even from very early on in the pandemic [ 42 ]. A study on the 3-year evolution of BS patients during the pandemic compared to prior to the pandemic also showed less weight loss during the pandemic [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
“…Factors that were associated with worse BI and eating outcomes during the pandemic included psychological, individual, social, and ED‐related characteristics. Psychological variables associated with worse outcomes included higher levels of worry, rumination, loneliness, anxiety, depression, stress, psychological distress, and fear of COVID‐19 (e.g., Akgül et al, 2021 ; Chan & Chiu, 2021 ; Frayn et al, 2021 ; Swami, Horne, et al, 2021 ); comorbidity of mental health concerns and childhood trauma (e.g., Castellini et al, 2020 ; Chan & Chiu, 2021 ); insecure attachment, lower self‐directedness, and poor coping strategies (e.g., Baenas et al, 2020 ; Haddad et al, 2020 ); poor emotion regulation (e.g., Félix et al, 2021 ; Flaudias et al, 2020 ; Machado et al, 2020 ); higher levels of uncertainty intolerance (e.g., Scharmer et al, 2020 ); and greater food insecurity (e.g., Christensen, Forbush, et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Social variables associated with worse outcomes included household arguments or family conflicts (e.g., Baenas et al, 2020 ; Castellini et al, 2020 ); change in living situation and access to usual support networks (e.g., Branley‐Bell & Talbot, 2020 ; Monteleone, Cascino, Marciello, et al, 2021 ); fear for the safety of loved ones (e.g., Castellini et al, 2020 ); longer social isolation and confinement (e.g., Coulthard et al, 2021 ; Haddad et al, 2021 ); perceived low quality of personal and therapeutic relationships (e.g., Cecchetto et al, 2021 ; Monteleone, Cascino, Marciello, et al, 2021 ); and exposure to COVID‐19‐related media and triggering messages regarding quarantine weight gain and exercise (e.g., Nutley et al, 2021 ; Vuillier et al, 2021 ). Evidence was mixed regarding participants' living situation, with some studies showing that living alone or living with fewer people was associated with less favorable outcomes (Félix et al, 2021 ; Pikoos et al, 2020 ), and other studies showing the detrimental effects of living with a higher number of adults in confinement (Haddad et al, 2020 ; Zeiler et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most published quantitative studies that have focused on the psychosocial impact of the epidemic on BS patients collected data during the first wave only [36,40], had no information on ethnic distribution of the sample [4,37,40,58], or were majority non-Hispanic White participants [36,60], and none collected data on substance use behaviors. Two international qualitative studies with sample sizes < 25 either were majority non-Hispanic White [6,61] or did not report ethnicity [7,62] and neither reported on substance use behaviors in BS patients. A history of BS is associated with increased substance, and this is thought to be due to a variety of psychosocial and physiological factors [8,9,[63][64][65][66].…”
Section: Discussionmentioning
confidence: 99%